Arterial Stiffness and Adult Onset Vasculitis: A Systematic Review - Lo Gullo, Alberto; Giuffrida, Clemente; Morace, Carmela; Squadrito, Giovanni; Magnano San Lio, Paola; Ricciardi, Luisa; Salvarani, Carlo; Mandraffino, Giuseppe (Frontiers in Medicine, 2022)
Chronic inflammation represents the cornerstone of the raised cardiovascular (CV) risk in patients with inflammatory rheumatic diseases (IRD), including vasculitis. Standardized mortality ratios in these patients are higher as compared to the general population, and the excess of premature mortality is due to early atherosclerotic events. Thus, IRD patients need appropriate CV risk assessment and management according to this CV disease (CVD) burden. Adequate control of CV risk is still lacking in usual care, but early diagnosis of silent and subclinical CVD is crucial to improve the long-term prognosis of these patients. Increased arterial stiffness may provide a pathophysiological link between inflammation and increased cardiovascular risk. Several noninvasive methods are now available to estimate artery stiffness in the clinical setting, including pulse wave velocity assessment. The independent predictive value of arterial stiffness for cardiovascular events has been demonstrated in general as well as in selected populations, and reference values adjusted for age and blood pressure have been suggested. Thus, arterial stiffness is an interesting biomarker for cardiovascular risk stratification. This systematic review summarizes the additional value that PWV measurement can provide in the setting of vasculitis, with a focus in the different clinical stages and CV risk prevention. This systematic review is registered with registration number: Prospero CRD42021259603.